Sosialisasi Pendidikan Pemilih Dan Partisipasi Masyarakat Terkait Pemilihan Umum Kepala Daerah di Kecamatan Selogiri - Retno Eko Mardani; Lita Tyesta Addy Listya Wardhani; Aziz Widhi Nugroho; Rengga Kusuma Putra; Fathul Hamdani; Bagus Hermanto; Daulat Nathanael Banjarnahor (Pusat Riset dan Inovasi Nasional, 2025)
Voter education is an important instrument in realizing a quality and sustainable democracy. Through the process of voter education socialization, it is hoped that the public can understand in depth their rights and obligations in the implementation of elections, as well as encourage active and responsible participation in the democratic process. Citizen participation in democratic social life must be based on adequate knowledge, critical reflection, and awareness of the rights and responsibilities as voters. A good understanding of the effectiveness of voter education socialization can shape a critical, rational, and independent attitude in exercising the right to vote, thereby strengthening the foundations of a clean and integrity-based democracy. This community service was carried out in the Selogiri District, Wonogiri Regency, with the aim of providing political education to the public regarding the importance of participation in the 2024 simultaneous regional head elections. Through a Participatory Action Research (PAR) approach, the community was actively involved as subjects in the activity process, not just as objects receiving information. Community service activities are carried out by integrating outreach into various village events, aimed at attracting residents to attend, interact, and directly discuss local political issues and forms of participation in the regional elections. Through these activities, it is hoped that the community will have a more comprehensive understanding of the importance of their role in determining the direction of regional policy through the regional elections. This education is also expected to raise awareness to vote based on conscience, without intervention or negative influences such as money politics, which has been a major challenge in every election at both the central and regional levels.